2020
DOI: 10.1101/2020.05.02.073890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the full kinetoplastids mitoribosome and insight on its large subunit maturation

Abstract: AbstractKinetoplastids are unicellular eukaryotic parasites responsible for human pathologies such as Chagas disease, sleeping sickness or Leishmaniasis1. They possess a single large mitochondrion, essential for the parasite survival2. In kinetoplastids mitochondrion, most of the molecular machineries and gene expression processes have significantly diverged and specialized, with an extreme example being their mitochondrial ribosomes Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In addition, the exit tunnel is blocked. In this regard, the present study is in agreement with the recently published work on Leishmania pre-mtLSU (Soufari et al 2020), which suggested that mL67, mL71, mL77, mL78, and mL81 represent assembly factors. The N-terminus of mL71 fills the exit tunnel, and its basic residues form electrostatic interactions with the rRNA that anchor the protein moiety.…”
Section: Assembly Of the Cp Is Linked To The Subunit Interface And L1supporting
confidence: 93%
“…In addition, the exit tunnel is blocked. In this regard, the present study is in agreement with the recently published work on Leishmania pre-mtLSU (Soufari et al 2020), which suggested that mL67, mL71, mL77, mL78, and mL81 represent assembly factors. The N-terminus of mL71 fills the exit tunnel, and its basic residues form electrostatic interactions with the rRNA that anchor the protein moiety.…”
Section: Assembly Of the Cp Is Linked To The Subunit Interface And L1supporting
confidence: 93%
“…During the transition from assembly intermediate state B to the mature LSU, which probably includes multiple steps and intermediates, all of the remaining assembly factors must leave such that the 12S rRNA core, including the PTC, can adopt its mature fold. These observations suggest that even the previously described mitoribosomal LSU (Ramrath et al, 2018) may represent a very late assembly intermediate with still-unstructured PTC and possibly some assembly factors still bound to the exit region of the large ribosomal subunit as described for the Leishmania tarentolae mitoribosome (Soufari et al, 2020). Multiple mitoribosomal proteins must join state B to form the missing parts of the LSU, in particular, the CP and elements of the L1 and the L7/ L12 stalks.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, mitochondrial ribosomes present important morphological differences with cytoplasmic ribosomes [ 27 ]. As cryo-EM technology allows to computationally sort ribosomes of different classes from the image data, the past few years have seen various new structures of mitochondrial ribosomes from yeast, plants, mammals and other eukaryotic cells [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In contrast with bacteria, from which mitochondria originate according to the endosymbiotic hypothesis [ 36 ], new or modified ribosomal proteins in mitoribosomes form an extended network around the ribosomal RNA.…”
Section: The Multiple Sources Of Heterogeneity In Ribosome Structumentioning
confidence: 99%